Kajian Penerapan GMP dan WISE Guna Peningkatan Higienitas Produk dan Produktivitas Pada UKM Amplang Samarinda - Theresia Amelia Pawitra; Farida Djumiati Sitania; Lina Dianati Fathimahhayati; Iklil Hilal; Rina Aivendar (Operations Excellence: Journal of Applied Industrial Engineering, 2022)
Hygiene and product safety were the main issue that need to be assured by food industries, including amplang industries in Samarinda. Furthermore, workers safety was also important for improving small industries’ productivity. This paper aimed to evaluate application of Good Manufacturing Practise (GMP) and Work Improvements in Small Medium Entreprise (WISE) in two small industries that produce amplang. GMP is a system that ensures products are consistently produced and controlled according to set quality standards. (i.e., BPOM standard). WISE is a programme to assist micro, small and medium-sized enterprises improve working conditions and productivity using simple, effective and affordable techniques. The GMP study showed that SME Y had GMP value higher than SME X (i68% and 55%). These two SMEs have used clean water to produce amplang and store raw materials, end products and hazardous materials properly. The drawbacks of these two SMEs are the need to improve recording and documentation as well as make SOPs for product withdrawals from the market. UKM X needs to make SOPs for the cleanliness of the production area and improve product labels. The results of the WISE study of these two SMEs have not provided appropriate PPE for workers and have not promoted occupational health. Procedure for mitigating fire hazard had not developed although fire was one of the risk factors in these two SMEs. Evacuation path had not been provided and even, SME X had not provided the fire extinguishers. Furthermore, ergonomic work station obliged to design especially for workers who sit cross-legged, designing cross-legged chair with back rest.